A comprehensive study of the incremental prognostic value of novel biomarkers in PARADIGM-HF (Bio-PREDICT-HF). (3rd October 2022) - McDowell, K; Simpson, J; Jhund, P S; Abraham, W T; Claggett, B; Cunningham, J; Desai, A S; Kober, L; Prescott, M; Rouleau, J L; Swedberg, K; Zile, M R; et al.
Abstract: Background: Although multiple novel biomarkers have individually been shown to predict outcomes in patients with HFrEF, the value of these over and above conventional clinical and laboratory variables, plus natriuretic peptides, is uncertain. Purpose: To test the incremental predictive value of 11 novel biomarkers added to a recent prognostic model 1 (PREDICT-HF) derived in PARADIGM-HF and validated in ATMOSPHERE and the Swedish heart failure registry. The PREDICT-HF model includes clinical variables, standard laboratory variables, and BNP or NT-proBNP. Methods: 1559 participants enrolled in PARADIGM-HF had all 11 biomarkers of interest measured. These reflected different pathophysiological pathways: (i) myocyte injury (high sensitivity cardiac troponin T), (ii) cardiac remodelling and inflammation (growth stimulation expressed gene 2, growth differentiation factor-15 and galectin-3), (iii) extracellular matrix remodelling (matrix metalloproteinase-2, matrix metalloproteinase-9, tissue inhibitor of metalloproteinase-1), (iv) neurohormonal pathways (aldosterone) and (v) renal dysfunction and injury (cystatin C, kidney injury molecule-1 and urinary albumin to creatinine ratio). The incremental prognostic value of these biomarkers was evaluated using Harrell's C statistic. Results: The mean age of participants studied was 67.3 (SD 9.9) years, 1254 (80%) were men and 1103 (71%) were in NYHA class II. During a median follow-up of 31 months, 197 patients died and 300 experienced the primary composite outcome (cardiovascular death or heart failure hospitalization). When each candidate biomarker (log unit) was added individually to the PREDICT-HF base model, GDF-15, ST2, TIMP1, cystatin C, hsTnT and UACR were independent predictors of all-cause mortality (Table 1). GDF-15, TIMP1, hs-TnT and cystatin C consistently increased the risk of both all-cause mortality and the primary outcome. Individuals who had all 4 biomarkers elevated (compared to none elevated) had the highest risk: HR for all-cause mortality 3.65 (2.01–6.64), p<0.0001. Adding these 4 biomarkers to the baseline PREDICT HF model improved the C statistic for all-cause mortality from 0.726 to 0.745. Conclusion: Several novel biomarkers provide meaningful additional prognostic information in patients with HFrEF. A multimarker approach incorporating biomarkers reflecting different pathophysiological pathways added most information. This approach may be useful in refining risk and targeting treatment. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): The PARADIGM-HF trial was funded by Novartis.J.J.V.M is supported by a British Heart Foundation Centre of Excellence Grant